Evaluation of UK Integrated Care Pilots: research protocol - Ling, Tom (Igitur, Utrecht Publishing & Archiving, 2010)
BACKGROUND: In response to concerns that the needs of the aging population for well-integrated care were increasing, the English National Health Service (NHS) appointed 16 Integrated Care Pilots following a national competition. The pilots have a range of aims including development of new organisational structures to support integration, changes in staff roles, reducing unscheduled emergency hospital admissions, reduced length of hospital stay, increasing patient satisfaction, and reducing cost. This paper describes the evaluation of the initiative which has been commissioned. STUDY DESIGN AND DATA COLLECTION METHODS: A mixed methods approach has been adopted including interviews with staff and patients, non-participant observation of meetings, structured written feedback from sites, questionnaires to patients and staff, and analysis of routinely collected hospital utilisation data for patients/service users. The qualitative analysis aims to identify the approaches taken to integration by the sites, the benefits which result, the context in which benefits have resulted, and the mechanisms by which they occur. METHODS OF ANALYSIS: The quantitative analysis adopts a ‘difference in differences’ approach comparing health care utilisation before and after the intervention with risk-matched controls. The qualitative data analysis adopts a ‘theory of change’ approach in which we triangulate data from the quantitative analysis with qualitative data in order to describe causal effects (what happens when an independent variable changes) and causal mechanisms (what connects causes to their effects). An economic analysis will identify what incremental resources are required to make integration succeed and how they can be combined efficiently to produce better outcomes for patients. CONCLUSION: This evaluation will produce a portfolio of evidence aimed at strengthening the evidence base for integrated care, and in particular identifying the context in which interventions are likely to be effective. These data will support a series of evaluation judgements aimed at reducing uncertainties about the role of integrated care in improving the efficient and effective delivery of healthcare.